Apical hypertrophic cardiomyopathy, a review of presentation, pathophysiology, diagnosis and natural course of the disease (Bangladesh Heart Journal, 2016)
Apical Hypertrophic Cardiomyopathy is an uncommon phenotype of hypertrophic cardiomyopathy. We present a review of best evidence on presentation, pathophysiology, diagnosis, outcomes and management for patients with apical hypertrophic cardiomyopathy.Bangladesh Heart Journal 2016; 31(1) : 29-36